The Case of Gnanathilaka Baddevithana: An Early Independent Investigation of One of Ian Stevenson’s Reincarnation Cases - Matlock, James G.; Weerasekera, Akila; Nahm, Michael (Journal of Scientific Exploration, 2024)
This paper analyzes one of the first reincarnation cases Ian Stevenson studied, in 1961, and reported in Twenty Cases Suggestive of Reincarnation. The case of Gnanathilaka Baddevithana had previously been investigated by H. S. S. Nissanka, who kept records of his interviews in writing or on tape, making this one of fewer than three dozen published cases with records produced before past-life memories were verified. Unfortunately, because the book Nissanka wrote about the case was published only in Sri Lanka, and not translated until 2001, his investigation is little known. Because Nissanka’s and Stevenson’s investigations were conducted independently, by comparing their reports, one can evaluate to what extent Stevenson’s oft-criticized practices of spending only a few days in the field and working through interpreters impacted his presentation and conclusions. These practices are shown to have led Stevenson to miss considerable detail but to have had no effect on his evaluation of Gnanathilaka’s case. This suggests that criticisms of Stevenson’s methods are misguided and that, if anything, some of the cases he reported may be phenomenologically richer and evidentially stronger than he presented them as being, rather than the reverse.